2016
DOI: 10.1080/13854046.2016.1224392
|View full text |Cite
|
Sign up to set email alerts
|

The 15-item version of the Boston Naming Test as an index of English proficiency

Abstract: The BNT-15 and BNT-10 can function as indices of English proficiency and predict the deleterious effect of LEP on neuropsychological tests with high verbal mediation. Interpreting low scores on such measures as evidence of impairment in examinees with LEP would likely overestimate deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 31 publications
2
13
0
1
Order By: Relevance
“…For professional/educational use there are guidelines for achievement (e.g., the Common European Framework of Reference for Languages), or tests (e.g., Test of English as a Foreign Language). For clinical investigation into bilingualism, both self-report, for example preference and scales ( Gasquoine, Croyle, Cavazos-Gonzalez, & Sandoval, 2007 ), NP tests—for example shortened versions of the Boston naming test (BNT) ( Erdodi, Jongsma, & Issa, 2017 )—and combinations of both ( Rosselli, Ardila, Santisi, et al., 2002 ) have been used.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For professional/educational use there are guidelines for achievement (e.g., the Common European Framework of Reference for Languages), or tests (e.g., Test of English as a Foreign Language). For clinical investigation into bilingualism, both self-report, for example preference and scales ( Gasquoine, Croyle, Cavazos-Gonzalez, & Sandoval, 2007 ), NP tests—for example shortened versions of the Boston naming test (BNT) ( Erdodi, Jongsma, & Issa, 2017 )—and combinations of both ( Rosselli, Ardila, Santisi, et al., 2002 ) have been used.…”
Section: Introductionmentioning
confidence: 99%
“…The cognitive effects of bilingualism have been investigated from the 1920s’ and onward, with early research often neglecting to account for factors that have later been shown to be relevant, such as rural–urban differences, gender, socioeconomics and proficiency ( Adesope et al., 2010 ; Peal & Lambert, 1962 ). Several methods to measure the balance between L1 and L2 have been suggested; for example dividing word flow in L1 by word flow in L2 ( Erdodi et al., 2017 ; Peal & Lambert, 1962 ; Shishkin & Ecke, 2018 ; Suarez, Gollan, Heaton, Grant, & Cherner, 2014 ). However, when dividing word flow between L1 and L2, current L1 capacity should be considered, as first language (L1) maintenance has been shown to be a factor ( Shishkin & Ecke, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7As stated in the Method section, participants were fluent in English but studies did not assess whether or not they were native speakers. Limited English proficiency has been determined to impact performance on neuropsychological tests (e.g., Erdodi, Jongsma, & Issa, 2017). …”
mentioning
confidence: 99%
“…Although basic verbal skills are required for the comprehension of the anchor words, the V-5 may be more transparent and accessible than traditional language-based symptom inventories. Existing research suggests that LEP has a strong deleterious effect on cognitive tests with high verbal mediation (Erdodi, Jongsma, & Issa, 2017; Erdodi, Nussbaum, Sagar, Abeare, & Schwartz, 2017; Gollan, Weissberger, Runnqvist, Montoya, & Cera, 2012; Sotelo-Dynega, Ortiz, Flanagan, & Chaplin, 2013) but not on visual-spatial tests (Boone, Victor, Wen, Razani, & Pontón, 2007).…”
Section: Discussionmentioning
confidence: 99%